The Responsibility of International Organisations and their Member States: an Overview of Outstanding Questions of Interpretation - Mohay, Ágoston (Pécs journal of international and European law, 2020)
The responsibility of international organisations has been on the agenda of the international com- munity for some time now, as evidenced among other things by the preparation of the Draft Ar- ticles on Responsibility of International Organizations (DARIO). However, the DARIO has not been adopted as a binding instrument, and various questions of interpretation remain. This brief problem-raising paper outlines some of the main contentious questions in this context and suggests further consideration of a number of related issues.